INFLUÃŠNCIA DA Ã‰POCA DE PLANTIO NA INFESTAÃ‡ÃƒO E DANO DE ð˜›ð˜©ð˜³ð˜ªð˜±ð˜´ ð˜µð˜¢ð˜£ð˜¢ð˜¤ð˜ª LINDEMAN, 1888 NA CULTURA DA CEBOLA (ð˜ˆð˜ð˜ð˜ªð˜¶ð˜® ð˜¤ð˜¦ð˜±ð˜¢ L.) - Sato, M. E.; Nakano, O. (REVISTA DE AGRICULTURA, 2020)
INFLUÃŠNCIA DA Ã‰POCA DE PLANTIO NA INFESTAÃ‡ÃƒO E DANO DE ð˜›ð˜©ð˜³ð˜ªð˜±ð˜´ ð˜µð˜¢ð˜£ð˜¢ð˜¤ð˜ª LINDEMAN, 1888 NA CULTURA DA CEBOLA (ð˜ˆð˜ð˜ð˜ªð˜¶ð˜® ð˜¤ð˜¦ð˜±ð˜¢ L.)